Benign Brenner Tumor Mixed with Mucinous Cystadenoma of the Left Ovary: Case Report and Literature Review, 2023 - Frezgi O; Tesfamichael T; Farah KH; Gebremariam H; Wahaballa YD; Tesfai B (Dove Medical Press, 2024)
Okbu Frezgi,1,2 Tiblets Tesfamichael,1 Khalid Hussein Farah,1,2 Hailemichael Gebremariam,3 Yasir D Wahaballa,4 Berhe Tesfai1,2 1Obstetrics and Gynaecology Department, Orotta National Referral Maternity Hospital, Ministry of Health, Asmara, Eritrea; 2Obstetrics and Gynaecology Department, Orotta College of Medicine and Health Sciences, Asmara, Eritrea; 3Department of Obstetrics and Gynaecology, Dekemhare Hospital, Ministry of Health, Dekemhare, Eritrea; 4Department Pathology, National Health Laboratory, Ministry of Health, Asmara, EritreaCorrespondence: Okbu Frezgi, Email lurgewra@gmail.comAbstract: Ovarian mucinous tumors mixed with Brenner tumors have rarely been reported. The coexistence of such epithelial tumors present histopathologic diagnostic difficulties. Here we report a 57-year-old postmenopausal woman who had experienced an abdominal distention and pain over a period of eight months. A physical examination revealed a grossly distended abdomen that reached the xiphoid process. A firm and mobile abdomino-pelvic mass with a smooth surface and a regular border was identified. Laboratory investigations showed a hemoglobin level of 13.54 g/dl and a serum cancer antigen 125 (CA125) of 97.3 U/mL. Trans abdominal ultrasonography revealed a massive complex mass originating from the left adnexa. A laparotomy was performed and a 10 kg left adnexal mass was removed intact. Histopathological analysis revealed mixed benign mucinous cystadenoma with a Brenner tumor of the left ovary. After surgery the patient showed marked clinical improvement, resumed her regular daily activities in three months and no recurrence has occurred during her long follow up. As the coexistence of these mixed tumors is not uncommon, a thorough pathologic evaluation is necessary and health professionals should be aware of the mixed occurrence of epithelial ovarian tumors.Keywords: co-existence, Brenner tumor, mucinous cystadenoma, ovarian tumor